Factors Associated with Breast Milk Quality Related to Cigarette Smoke Exposure: A Cross Sectional Study in Balai Agung Health Center, Musi Banyuasin Regency - Marlini; Manisah Manisah; Icuk Muhammad Sakir (Poltekkes Kemenkes Surabaya, 2026)
The quality of breast milk is an important factor in supporting infant growth and health, but it can be influenced by environmental and behavioural factors, including exposure to cigarette smoke. This study aims to analyse the relationship between exposure to cigarette smoke, exposure to household cigarette smoke, and breastfeeding patterns with breast milk quality in breastfeeding mothers in the working area of the Balai Agung Community Health Centre, Musi Banyuasin Regency. This study used an analytical observational design with a cross-sectional approach involving 60 breastfeeding mothers of infants aged 0–6 months who were selected purposively. Data were collected through structured interviews and breast milk quality tests in the laboratory, then analysed descriptively and bivariately using statistical tests with a significance level of 5%. The results showed that the majority of respondents were exposed to cigarette smoke (63.3%) and lived with smokers at home (70.0%). Mothers exposed to cigarette smoke had a nine times greater risk of producing poor-quality breast milk compared to mothers who were not exposed (OR = 9.00; p = 0.002). Exposure to cigarette smoke in the household was also significantly associated with breast milk quality (OR = 6.00; p = 0.015). In addition, non-exclusive breastfeeding patterns increased the risk of poor-quality breast milk by more than five times (OR = 5.44; p = 0.004). This study concluded that exposure to cigarette smoke and breastfeeding patterns are important determinants of breast milk quality, so efforts to protect breastfeeding mothers from cigarette smoke and strengthen exclusive breastfeeding practices need to be prioritised in primary health care services.